Identifying owner management decisions surrounding end-of-life care and euthanasia of geriatric horses in New Zealand : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science in Agricultural Science, School of Agriculture and Environment, Massey University, Manawatu, New Zealand - Anderson, Lily (Massey University, 2025)
A geriatric horse is defined by its chronological, functional, or demographic age. Despite advancement on veterinary care and improved husbandry practice, death is inevitable, and geriatric horses will progressively have a decreased quality of life as they age. Regardless of a horses functional or productive benefit to humans, moral and legal responsibilities are placed on the owner to make management and end-of-life decisions in the best interest of the horse’s welfare. Few studies have explored characteristics of New Zealand horse owners, identification of the national geriatric horse population, or factors which influence owner decision making. There is also greater attention needed on the common practice of euthanasia and disposal methods in New Zealand with increasing international legislation and regional restraints. Therefore, this study aimed to describe owner management decisions surrounding end-of-life care and euthanasia of geriatric horses in New Zealand. An online survey collected data from 1,207 respondents. Over half (53%) of owners were based in Auckland, Waikato, and Manawatu-Wanganui. Most respondents identified as female (n=1,178, 98%), and nearly two thirds owned a geriatric horse (60%). Geriatric horses (>15 years) were a median of 17 years old (IQR 16-22) and were visited by their owner twice a day (n=454, 70%). Most respondents had thought about a euthanasia plan for their horse (n=821, 77%), with veterinary administered overdose of barbiturates (n=886, 83%), and burial (n=774, 72%) preferred methods for euthanasia and disposal. On a scale from 0–5 (with 5 most influential) pain and poor prognosis were rated by owners as most influential when making end-of-life decisions for their horse (median score = 5/5, IQR 5–5). This study highlighted that owners are driven by their emotional bond with their horse and are largely dependent on veterinarian support when making end-of-life, euthanasia, and disposal decisions.
Keywords: 300306 Animal welfare; 300302 Animal management